2018
DOI: 10.1007/s00592-018-1111-5
|View full text |Cite
|
Sign up to set email alerts
|

The association of short-term memory and cognitive impairment with ghrelin, leptin, and cortisol levels in non-diabetic and diabetic elderly individuals

Abstract: Fasting plasma ghrelin and cortisol levels may be markers of cognitive decline and memory loss. It is possible that adjusting their levels may have a therapeutic effect, and this should be investigated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In clinical studies, most studies examining the link between cortisol levels and global cognitive performance among non-demented older adults found that higher cortisol levels have been associated with poorer overall cognitive performance (Lupien et al, 2007; Lee B.K. et al, 2008; Ouanes et al, 2017a; Sang et al, 2018). Likewise, most (Beluche et al, 2010; Geerlings et al, 2015; Segerstrom et al, 2016; Ouanes et al, 2017a,b; Echouffo-Tcheugui et al, 2018), even though not all (Lee B.K.…”
Section: Glucocorticoid Receptors and Cortisol Effects On Cognitionmentioning
confidence: 99%
“…In clinical studies, most studies examining the link between cortisol levels and global cognitive performance among non-demented older adults found that higher cortisol levels have been associated with poorer overall cognitive performance (Lupien et al, 2007; Lee B.K. et al, 2008; Ouanes et al, 2017a; Sang et al, 2018). Likewise, most (Beluche et al, 2010; Geerlings et al, 2015; Segerstrom et al, 2016; Ouanes et al, 2017a,b; Echouffo-Tcheugui et al, 2018), even though not all (Lee B.K.…”
Section: Glucocorticoid Receptors and Cortisol Effects On Cognitionmentioning
confidence: 99%
“…Intrahippocampal ghrelin increases nitric oxide synthase (NOs) to induce short-term and long-term memory improvement [86] ( Figure 7). e lower level of fasting ghrelin and inhibition of ghrelin signaling in humans were associated with memory loss and cognitive impairment [87,88], even though other studies showed that ghrelin has no effect on memory; instead, it modulates encoding-related brain functions without enhancing memory formation [89].…”
Section: Octanoylated Mouse Ghrelinmentioning
confidence: 99%
“…Each participant's height and weight were measured and used to calculate the body mass index (BMI). The kits used for ghrelin and leptin analyses were similar to those used in our previous studies [42].…”
Section: Evaluation Of Physiological Indicesmentioning
confidence: 99%